Efektivitas Buku Ajar Pembelajaran Membaca Bermuatan Cerita Rakyat Melayu Riau - Gusmalinda, Indah; Asnawi, Asnawi (UIR PRESS, 2023)
This research uses an experimental research method, and the product developed in this study is a textbook for reading instruction that incorporates Malay Riau folklore stories. The aim of the study is to enhance students' understanding of the subject matter being taught and improve their learning outcomes. The data analysis results indicate that the reading instructional textbook containing Malay Riau folklore stories is effective in improving students' learning outcomes. The data analysis results demonstrate that the textbook has a significance level smaller than 0.05, which means that the book significantly influences students' learning outcomes. The posttest results in the experimental group show higher average scores compared to the control group. Hypothesis testing also indicates a significant difference between the posttest results of the experimental and control groups. Based on these results, it can be concluded that the reading instructional textbook incorporating Malay Riau folklore stories is effective.